Academics’ Perception On The Transformation Of University Colleges To Universities: A Pilot Study In A Malaysian University College - Sara Asmawati, Shariffuddin; Jamal Rizal, Razali; Ismi Safia Adilah, Ibrahim; Sharifah Sakinah, Syed Abd Mutalib (2017)
The main objective of this pilot study was to obtain preliminary data for the main study. In the paper, the perception of the academics at a Malaysian university college on the transformation of the university college towards university was examined using a questionnaire developed for the purpose of the study. The questionnaire items were utilized to examine the perception of the academics on the problems in eight main areas including performance management and promotion; role overload, role conflict or both; financial remuneration; research and teaching; work uncertainty; training and development; equipment and working conditions and leadership and governance. Other sections of the questionnaire also investigate the effects of the problems to the academics and supports provided. The results revealed that majority of the academics faced problems in five main areas related to their work scope as teachers and researchers. They also agreed that the problems affect them in achieving personal and university institutional KPI, their teaching and research workload, motivation and job satisfaction. In fact, supports were provided by the management to the academics for the development of six elements. However, the results prove that there were room for improvements on the supports provided by the management of the university college so that the academics are able to perform and achieve more their personal and institutional key performance indicators.